Ozone intensities in the rotational bands. (March 2019) - Birk, Manfred; Wagner, Georg; Gordon, Iouli E.; Drouin, Brian J.
Highlights: Reconciliation of ozone microwave data in the HIRAN and JPL databases. Explanation of theory for centrifugal distortion of permanent dipole. Far-infrared absolute intensity measurement. Impact of intensity adjustment for ozone remote sensing. Abstract: This note provides a citable reference to a database reconciliation effort for ozone pure rotational intensities. The permanent dipole moment and theoretical adjustments for centrifugal distortion are utilized in a predictive calculation that is compared to experimental measurements. This prediction has been available in the JPL spectral line catalog since 2005, but has been at odds with the HITRAN database, which was originally based on an atlas provided by Flaud (HITRAN 1992) and subsequently scaled by 4% (HITRAN 2004). Using a modified partition function and isotopic abundance factor, the JPL 2005 prediction has now been utilized to create a self-consistent entry as an interim update to the HITRAN2016 database. Ramifications of the intensity change for users of HITRAN versions 2004–2012 are discussed. New pure rotational intensity measurements were carried out supporting the validity of the JPL 2005 database.